2006
DOI: 10.1080/02699200500363724
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the acquisition of vowel phonemes by pre‐linguistically deafened cochlear implant users learning Cantonese

Abstract: This paper describes the development of vowel inventories in 12 pre-linguistically deafened Cantonese-speaking cochlear implant users. The aim of the research was to understand the role of linguistic, perceptual and articulatory factors in determining the rate and order of vowel acquisition in this population of children. Rate and order of vowel acquisition were reported against two criteria. The "targetless" criterion for production required at least two correct productions of a vowel in a sample of speech. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Thus, order of acquisition is similar in Blanca and the NH children, but the rate of acquisition is slightly slower in Blanca. These results are similar to those described by other reseachers (see Serry & Blamey, 1999;Barry, Blamey, & Fletcher, 2006). Figure 4 shows the ratio of correct words, mispronounced words, and non-intelligible words.…”
Section: Phonemic Inventory and Intelligibilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, order of acquisition is similar in Blanca and the NH children, but the rate of acquisition is slightly slower in Blanca. These results are similar to those described by other reseachers (see Serry & Blamey, 1999;Barry, Blamey, & Fletcher, 2006). Figure 4 shows the ratio of correct words, mispronounced words, and non-intelligible words.…”
Section: Phonemic Inventory and Intelligibilitysupporting
confidence: 92%
“…The authors found the trend in phone acquisition was the same as that of NH children, though the process occurred at a slower rate. Barry, Blamey, and Fletcher (2006) obtained similar results with Cantonese children implanted at a mean age of 4;5 years.…”
Section: Variability Within Linguistic Domainssupporting
confidence: 87%
“…However, it remains unclear up to what point the development of productive speech and language is typical in children implanted at an early age. Some indications of typical, though possibly slow, development are : a typical order of phoneme acquisition (Serry & Blamey, 1999 ;Barry, Blamey & Fletcher, 2006;Moreno-Torres & Torres, 2008); and typical error patterns in the production of consonant clusters (Kim & Chin, 2008 ;Adi-Bensaid & Ben-David, 2010). Furthermore, different researchers have found evidence of either atypical or typical development.…”
Section: Introductionmentioning
confidence: 99%
“…Tone differentiation in each speaker groups' rising tones was expected to cluster closer to the y-axis, as they have higher offsets than onsets, whereas falling tones would cluster closer to the x-axis. An example of this is seen in the tone production of Cantonese by children with cochlear implants [1,2]. In these studies, ellipses were drawn to visualise the space for each tone type.…”
Section: Plots Of F0 Onsets and Offsetsmentioning
confidence: 99%
“…Three further analyses have determined how tones were differentiated within the tonal space and among tonemes, based on previous studies [1,2]. The parameters calculated consisted of the axes' lengths, the areas of the tonal ellipses and the distances between the centre points of each ellipsis.…”
Section: Plots Of F0 Onsets and Offsetsmentioning
confidence: 99%